Cosmology in the Universe with Distance Dependent Lorentz-Violating Background - C. A. G. Almeida; M. A. Anacleto; F. A. Brito; E. Passos; J. R. L. Santos (Advances in High Energy Physics)
We consider a cosmological setup with inflaton in the presence of a redshift dependent Lorentz-violating time-like background to address the inflationary regime and other phases of the Universe. We also show that the regime of dark energy at large distances (low redshifts) is essentially dominated by the presence of the Lorentz-violating background.